1998
DOI: 10.1007/bf02445277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elementary proline-containing peptides on functional activity of anticoagulation system and primary homeostasis

Abstract: Elementary proline-containing peptides being added to rat platelet-rich plasma or platelet suspension in concentrations of 10-1-10 -7 mg/ml elicit a considerable antiplatelet effect. Efficiency of inhibition of platelet aggregation increases in the following order: ProGly>Pro-Gly-Pro>Gly-Pro-Gly-Gly. Intravenous injection of these peptides activates blood anticoagulation system in experimental animals. Key Words: platelet aggregation; elementary proline-containing peptidesThere are experimental data on various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Studying the dynamics of hemostatic parameters after intranasal administration of Pro-Gly-Pro showed that the anticoagulant effect of this peptide developed over the first minutes after treatment [2] and persisted for 3 or even 5 h. Hemostatic parameters returned to normal 24 h after administration of the peptide. Peptide-induced changes in the enzymatic and nonenzymatic fibrinolytic systems were most persistent.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Studying the dynamics of hemostatic parameters after intranasal administration of Pro-Gly-Pro showed that the anticoagulant effect of this peptide developed over the first minutes after treatment [2] and persisted for 3 or even 5 h. Hemostatic parameters returned to normal 24 h after administration of the peptide. Peptide-induced changes in the enzymatic and nonenzymatic fibrinolytic systems were most persistent.…”
Section: Resultsmentioning
confidence: 91%
“…Glyprolines, regulatory proline-containing peptides, modulate several processes in the organism, play a role in inhibition of blood coagulation, normalize impaired cerebral circulation, and stimulate nerve regeneration [1,2,10]. Peptides Pro-Gly-Pro and Pro-Gly produce an antithrombotic effect [7], which is related to antiplatelet, anticoagulant, and fibrinolytic activities.…”
mentioning
confidence: 99%
“…Simple proline-containing peptides exhibit anticoagulant, fi brinolytic, and antiplatelet effects in the blood stream, stimulating the function of the blood anticoagulation system [3,6]. On the other hand, many regulatory peptides are characterized by wide spectra of biological activities and among other things are involved in the maintenance of normal homeostasis during stress [1,2].…”
mentioning
confidence: 99%